Assessing the neuroprotective potential of Eucalyptus globulus essential oil in a 6-hydroxydopamine rat model of Parkinson's disease - Aracely Janneth Naranjo-Viteri; Matías Jávega Cometto; Matías Caverzan; Leandro Gabriel Champarini; María Paula Zunino; Rogelio E. Abburra; Claudia B. Hereñú; Rosana Crespo (Pharmacological Research - Modern Chinese Medicine)
Introduction: Essential oil (EO) of eucalyptus has been commonly used as a traditional Chinese medicine to treat illnesses such as influenza, dysentery and eczema, and it is widely used in the pharmaceutical industry. However, its neuroprotective effects have not been fully demonstrated. Given the rising prevalence of the neurodegenerative disorder, Parkinson's disease, in aging populations, this study aims to investigate the effect of Eucalyptus globulus EO (EuEO) in a rat Parkinson model induced by bilateral lesion with the neurotoxin, 6-hydroxydopamine (6-OHDA). Methods: EuEO composition was determined by GC–MS. Wistar rats were treated with EuEO (25 mg/kg, i.p) for 36 days, and behavioral tests (Barnes maze, wire mesh ramp, and grip strength) were performed 18 days after 6-OHDA application. We evaluated tyrosine hydroxylase (TH) and dopamine transporter (DAT) expression in the brain caudate-putamen unit; inflammatory cytokine (TNF-α, IL-6) expression in the hippocampus; liver, kidney, and gut histology; serum parameters; and hepatic lipid content. Results: Our findings indicate that EuEO is mainly composed of 1,8-cineole (81.8 %) and that, in the parkinsonian rats, it improved impairments in spatial memory, motor performance, and strength; increased TH and DAT protein content; decreased TNF-α expression; diminished liver lipid content and body weight gain without changes in the rats’ food/water consumption or their serum lipid levels; diminished transaminase and alkaline phosphatase activity, and the albumin/globulin ratio. Discussion: Although 1,8-cineole is a well-documented bioactive compound, further research is required to evaluate its potential synergistic or additive interactions with minor components. Our findings highlight the remarkable neuroprotective potential of EuEO and encourage further research of this very promising therapeutic alternative.